Memorandum of understanding between Universiti Teknologi MARA and Persatuan Wanita UiTM (PEWANI) / Fakulti Pendidikan - Universiti Teknologi MARA, Fakulti Pendidikan (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.